Enhancing Corrosion Resistance and Tribomechanical Characteristics of Powder Coatings via the Integration of Functionalized HF‐Free MXene Reinforcements - Ziba Nazarlou; Naeimeh Sadat Peighambardoust; Peyman Lahe Motlagh; Umut Aydemir (Advanced Materials Interfaces)
Abstract MXene, a new generation of 2D materials, is gaining attention for anti‐corrosion applications due to its large surface area, electrical conductivity, and self‐healing properties. Its low shear strength and self‐lubricating properties enhance wear resistance. Herein, silane functionalized HF‐Free MXene nanosheets “MS‐f_Ti3C2 and MS‐f_Ti3C2@Zn” synthesized through the molten salt method are integrated into the environmentally sustainable powder coating. The electrochemical tests indicate that a powder coating containing a well‐dispersed 1.5 wt.% f_Ti3C2@Zn nanosheets exhibit the highest polarization resistance (1.1 × 106 Ω cm2), lowest Icorr (2.15 × 10−8 A cm−2) and superior anti‐corrosion performance after 42 days of immersion in 3.5 wt.% NaCl. The polarization resistance (Rp) and corrosion current (Icorr) of the untreated coating are measured to be 1.6 × 103 Ω cm2 and 1.6 × 10−5A cm−2, respectively. In addition, the incorporation of MXene material reduces crack development and spalling, and enhances wear resistance during the friction process. The loading of 1.5 wt.% f_Ti3C2@Zn reduces the coefficient of friction (COF) and improves wear rate by 45% and 51%, respectively Analysis of composites via nanoindentation reveals such enhanced mechanical properties. This study presents an effective and sustainable approach to improve the mechanical, tribological, and long‐term corrosion protection of organic coating, thereby exhibiting great potential for using HF‐Free MXene as a multipurpose additive.